Iklim Ekstrim Dan Perubahan Iklim Di Kabupaten Jember - Jefri Anggara (Jurnal Ilmiah Inovasi, 2017)
The increase in extreme climate events in recent years is the impact of climate change.Extreme climatic events trigger anomalies of the weather causing climateclassification mismatches.This study aims to determine the pattern of rainfall in the influence of extreme conditions, as well as changes in Oldeman climate classification in Jember Regency, based on rainfall data for the last 30 years.The results showed (a) the pattern of below normal rainfall in Jember Regency influenced by the incidence of El Nino, while rainfall above normal influenced by La Nina, (b) rainfall in every decade tends to increase in the last 30 years, (c) there has been a change in the type of Oldeman climate classification in most areas of Jember Regency to be drier than in the 1975 with loss of climate typesof B1, B2 and C2.